Analisis Fishbein Dalam Menciptakan Pengelolaan Pariwisata Berkelanjutan (Studi Pada Museum Kotagede) - Muhammad Zuhal Firmansyah; Agung Sulistyo; Amiluhur Soeroso (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
Museums are often perceived as places that are unattractive, unclean, and lack explanation, so interest in visiting museums is still low. This condition is different from the Kotagede Museum, which experienced a growth in the number of visitors. In an effort to maintain existence, managers need to satisfy visitors' wants and needs. This situation is in accordance with one of the conditions for creating sustainable tourism, which takes into account visitor satisfaction. This research aims to determine visitors' attitudes towards the Kotagede Museum. This research uses a mixed method through fishbein analysis. The Fishbein multi-attribute attitude model is used as a data analysis technique. Questionnaires, interviews, and observations were used as data collection techniques. Questionnaires were distributed to 372 respondents and reinforced with open interviews to explore respondents' answers. The research results stated that visitors' attitudes towards the Kotagede Museum were positive, with a score of 94.313. The attitude value is in the right position of the cut-off point, between the range of agree and strongly agree. The aesthetic building attribute got the highest score (20.599), and the strategic location attribute got the lowest score (16.855). Kotagede Museum managers can maintain attributes that get high scores and improve the quality of attributes that get low scores.